(untitled) (Biological Sciences - PJSIR, 2000)
The Kora Gypsum Deposit (KGD) is present in the western Salt Range near Daudkhel in District Mianwali. Petro- graphic and geochemical studies of KGD have been made to evaluate the nature of deposit and characteristics of the depositional environment. The gypsumgrades into Sakesar limestoneofUpper Eocene age.It is inferred that KGD is asulphate faciesofSakesarlimestone,formedinabarredbasin.Traceelementanalysesofgypsumandlimestone show nearly similardistribution patterns,indicating samegeochemicalenvironment.The lowMg, poor Fe andabsence of K fromthegypsum samples indicateDeepBasin DeepWater(DBDW)condition.The presenceofclay,high chaJcophile elements (Zn, Cu and Ni) and sedimentary structures observable in the field also suggest a DBDW model. The thin section studies and geochemical investigations communicate that initially gypsum was precipitated either due to evaporation ormixing of differentbrines.DehydrationofgypsumintoanhydriteoccurredduringMiocene duetothick successionofoverlying Siwaliks.ThePlioceneHimalayantectonicscausedupliftingofthe areaandsubsequenterosion and removal of overburden brought these anhydrite beds to near surface conditions, where they were converted into gypsum due to rehydration from groundwater.